2015
DOI: 10.2174/1871527314666150116110212
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Extends Lifespan and Reduces Proteotoxicity in C. elegans Alzheimer’s Model

Abstract: Aging is a process of progressive decline in physiological functions resulting in increased vulnerability to diseases and death. Aging results in increased rates of age related disorders like neurodegenerative diseases, cardiovascular diseases, diabetes, cancer, arthritis etc. Modulation of insulin signaling, protein aggregation, stress, free radical damage and inflammation are the major causes for deleterious changes resulting in aging. Many studies are being undertaken to find novel compounds which can impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…In the case of the flavolignan isomers silymarin, the effect appeared to be dose dependent, since 25 and 50 µM increased the worm's lifespan, while 100 µM shortened it (49) .…”
Section: Flavonoids and The Lifespan Of The Worm Caenorhabditis Elegansmentioning
confidence: 97%
“…In the case of the flavolignan isomers silymarin, the effect appeared to be dose dependent, since 25 and 50 µM increased the worm's lifespan, while 100 µM shortened it (49) .…”
Section: Flavonoids and The Lifespan Of The Worm Caenorhabditis Elegansmentioning
confidence: 97%
“…A previous study has shown silibinin to inhibit anaplastic large cell lymphoma through suppressing pathways involving STAT3, MEK/ERK and AKT (33). Additionally, silymarin treatment has also been reported to increase the lifespan in Caenorharbditis elegans (34). It is important to mention here that silymarin is an extract from milk thistle seed containing silibinin, isosilibinin, silychristin, silydianin and others, but silibinin is considered the prominent active ingredient (35).…”
Section: Discussionmentioning
confidence: 95%
“…The beneficial effects of NDS are probably due to the well-documented anti-oxidative actions of curcumin, although a synergistic action of all polyphenolic compounds contained in NDS has to also be considered. In fact, antioxidant and neuroprotective effects have been reported for silymarin and chlorogenic acid as well [72,73]. Figure 1 summarizes the main actions responsible for the neuroprotective effects of curcuminoids.…”
Section: Curcuminoidsmentioning
confidence: 99%
“…The ability to slow the progression of neurodegeneration was also tested in CL4176 Caenorhabditis elegans, a model for AD. The results demonstrated that silymarin treatment significantly reduced the expression of amyloid β-protein (Aβ1-42) in muscle tissues of C. elegans via enhancing resistance to oxidative stress [72]. In rats, silymarin administration can improve ethanol- Nevertheless, clinical trials revealing any beneficial effects of curcuminoid administration for the treatment of AD are few and controversial [77][78][79].…”
Section: Silymarinmentioning
confidence: 99%